Electrochemical and structural characterization of heat-treated Cr3C2-NiCr coatings - Suegama, P. H.; Espallargas, N.; Guilemany, J. M.; Fernandez, J.; Benedetti, Assis Vicente [UNESP] (Electrochemical Soc Inc, 2006)
The influence of heat-treatments on the electrochemical behavior of thermal spray Cr3C2-NiCr coatings prepared by high velocity oxygen fuel (HVOF) was studied in NaCl solution, at 25 degrees C, using open-circuit potential (E-OC) and electrochemical impedance spectroscopy (EIS) measurements. Coating characterization were performed before and after the heat-treatments and electrochemical tests by scanning electron microscopy, X-ray diffraction, and Auger electron spectroscopy. In addition to the changes in the original powder composition occurring during HVOF process, heat-treatment performed at 450 degrees C caused no significant changes in electrochemical response compared with untreated sample, and at 760 degrees C the main difference was the formation of a thin and defective layer of Cr2O3 at the coating surface, which increased the total impedance at the first day of immersion. Higher influence on the electrochemical was noted for samples treated at 880 degrees C, which also showed higher E-OC and total impedance, and lower corrosion current. This behavior was interpreted considering the formation of a chromium oxide layer on the coating surface, dissolution and decomposition of smaller carbide particles and their surface enrichment with Cr due to C diffusion and dissolution into the matrix, and possible Ni, Cr, and Fe diffusion to coating/substrate interface. (c) 2006 the Electrochemical Society.